IMAGING FINDINGS OF HEPATIC FOCAL NODULAR HYPERPLASIA IN GD-EOB-DTPA VS. GD-BOPTA-ENHANCED MRI - Federica Di Naro (Euromediterranean Biomedical Journal, 2012)
Focal nodular hyperplasia (FNH) is a benign focal lesion of the liver. Magnetic resonance imaging (MRI) plays a key role in the detection and characterization of focal hepatic lesions, thanks to the widespread availability of conventional contrast media, especially liver-specific media such as Gd-BOPTA (Multihance, or Gadobenate Dimeglumine) and GdEOB-DTPA (Primovist, or Gadoxetic Acid) that are selectively accumulated in hepatocytes and partially excreted by the biliary system. There are no significant differences in FNH enhancement, neither during the dynamic phase nor during the liver-specific phase of MRI, following the infusion with GD-BOPTA or GD-EOB-DTPA.